Case Report: Rare Homozygous RNASEH1 Mutations Associated With Adult-Onset Mitochondrial Encephalomyopathy and Multiple Mitochondrial DNA Deletions - Manini, Arianna; Caporali, Leonardo; Meneri, Megi; Zanotti, Simona; Piga, Daniela; Arena, Ignazio Giuseppe; Corti, Stefania; Toscano, Antonio; Comi, Giacomo Pietro; Musumeci, Olimpia; Carelli, Valerio; Ronchi, Dario (Frontiers in Genetics, 2022)
Mitochondrial DNA (mtDNA) maintenance disorders embrace a broad range of clinical syndromes distinguished by the evidence of mtDNA depletion and/or deletions in affected tissues. Among the nuclear genes associated with mtDNA maintenance disorders, RNASEH1 mutations produce a homogeneous phenotype, with progressive external ophthalmoplegia (PEO), ptosis, limb weakness, cerebellar ataxia, and dysphagia. The encoded enzyme, Ribonuclease H1, is involved in mtDNA replication, whose impairment leads to an increase in replication intermediates resulting from mtDNA replication slowdown. Here, we describe two unrelated Italian probands (Patient 1 and Patient 2) affected by chronic PEO, ptosis, and muscle weakness. Cerebellar features and severe dysphagia requiring enteral feeding were observed in one patient. In both cases, muscle biopsy revealed diffuse mitochondrial abnormalities and multiple mtDNA deletions. A targeted Next Generation Sequencing analysis revealed the homozygous RNASEH1 mutations c.129-3C>G and c.424G>A in Patient 1 and 2, respectively. The c.129-3C>G substitution has never been described as disease-related and resulted in the loss of Exon 2 in Patient’s 1 muscle RNASEH1 transcript. Overall, we recommend implementing the use of high-throughput sequencing approaches in the clinical setting to reach genetic diagnosis in case of suspected presentations with impaired mtDNA homeostasis.